Chlorine Effects of Heterocyclic Ring‐Based Donor Polymer for Low‐Cost and High‐Performance Nonfullerene Polymer Solar Cells. Issue 7 (15th May 2019) - Jeon, Sung Jae; Han, Yong Woon; Moon, Doo Kyung
Abstract : The industrialization of polymer solar cells (PSCs) requires high‐performance devices with high efficiencies and stabilities. Although high‐performance PSCs are achieved via outstanding research into their component materials and device structures, several challenges still need to be overcome, including the synthetic complexity (SC) of producing the active material. In this study, donor polymers based on two heterocyclic rings and simple donor–acceptor structures are designed to obtain a low‐cost material for PSCs. An inexpensive and high‐performance donor polymer P(Cl) is realized by the introduction of a chlorine‐atom substitution. P(Cl), which has lower SC than commercial donor polymers, has many advantages, such as high overall yield, low number of synthetic steps, and inexpensive raw materials. Moreover, fabricated P(Cl)‐based PSCs exhibit a high power‐conversion efficiency (PCE) of 12.14%. Through the shelf protocol of the international summit on organic photovoltaics stability in dark testing‐1 (ISOS‐D‐1) measurements, superior long‐term stability is demonstrated for P(Cl)‐based devices both without and with encapsulation; their PCEs are maintained at 91% and 100% of the initial values for up to 2002 and 2858 h, respectively, under ambient conditions. Therefore, P(Cl) is a promising donor polymer for commercial PSC applications. Abstract : A low‐cost, high‐yield synthesis of a chorine‐substituted thiophene donor polymer material P(Cl) is presented. The material is characterized, and its performance within a polymer solar cell (PSC) with a nonfullerene acceptor is evaluated. Excellent power‐conversion efficiency combined with a low synthetic complexity is demonstrated for P(Cl), and hence, it is a promising candidate for the development in commercial PSC applications.